Fecundity and Almodóvar? Sexual Ethics and the Specter of Catholicism - McMahon, Christopher (The journal of religion and film, 2006)
The famed Spanish film maker Pedro Almodóvar has spent much of his film career narrating stories which subvert the Francoist-Catholic ideology of mid-twentieth century Spain, particularly its account of sex and family. But in several of his recent films prior to Bad Education both homosexual and heterosexual characters struggle with questions of sexuality and birth. As these themes are subtly and dramatically presented they exert what one may identify as the 'spectral force' of Catholicism. As such, this essay suggests that these films may offer resources for Catholics to engage the critical questions concerning homosexuality in the life of the church.